Avaliação de efeitos terapêuticos e nutricionais da farinha de Passiflora edulis (maracujá - amarelo) em estudos pré-clinícos com ratos - Figueiredo, Dandara Antonia Felizardo de (2013)
Species of genus Passiflora are documented in the literature as an anxiolytic and sedative agent. Although many studies assess the behavioral action of extracts of leaves of Passiflora, few studies have evaluated their behavioral and physiological effects of Passiflora edulis barks in the form of treatment and in natura. From this, the present research aimed to assess the behavioral and physiological effects of treatment with the bark flour of Passiflora edulis, thereby investigating their potential nutraceutical properties. Were utilized 40 adult male Wistar rats randomized into four groups: Control Group - CG, Albedo Group - AG, Flavedo Group - FG, Albedo + Flavedo Group AFG, which were treated (p.o) for 30 days with the bark of albedo flour (130mg/kg), diluted in filtered water and administered by gavage technique, flavedo and full bark of Passiflora edulis, albedo associated with flavedo. Weight gain and food consumption were monitored throughout the treatment. Behavioral changes were analyzed at the end of treatment (30 days) for testing in the Elevated Plus Maze, validated method to explore the neurobiological basis of anxiety, of Open Field, which evaluates the exploratory activity of animals and by means of Rota-Rod, which analyzes the coordination of animals. In the Elevated Plus Maze only the AFG (62,89 ± 22,06) had a greater time(s) spent in the open arms of the apparatus compared to CG (12,67 ± 5,09; p <0,05). The AFG (148,1 ± 26,02) in Open Field showed greater immobility time compared to both GC (24,00 ± 7,02; p <0,001) and the experimental groups treated with the albedo flour only (29,30 ± 7,57; p <0,001) and flavedo flour (39,00 ± 10,42; p <0,001). The median spaces traversed by the animals of AFG was 10,5 (percentile 6,5 - 20). Having these a smaller number of ambulation that GC, in which was observed a median of 31,5 (percentile 31 - 36,5), p <0,001 and the other experimental groups, AG and FG, which had a median of 32,0 (percentile 31 - 36,5) p <0,001 and 29,0 (percentile 24 - 38,5), p <0,01. The weight gain (g) of animals of AFG (79,6 ± 5,60) was 22,3% lower than the CG (102,8 ± 1,52). The animals of AG (86,3 ± 3,22) reduced weight gain by 16%. The treatments resulted in no anxiolytic nor alter the coordination of the animals but sedative effects were observed in AFG.Dietary intake of treated animals was not changed, but the weight gain was decreased in both animals the AFG, as in AG. Therefore, it is concluded that the complete bark flour of Passiflora edulis has sedative effects, without causing anxiolytic and muscle relaxation effects; and aids in reducing body weight gain, thus presenting nutraceutic properties.